2017
DOI: 10.1002/2015jg003297
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Community Land Model parameters for an improved assessment of net carbon fluxes at European sites

Abstract: The Community Land Model (CLM) contains many parameters whose values are uncertain and thus require careful estimation for model application at individual sites. Here we used Bayesian inference with the DiffeRential Evolution Adaptive Metropolis (DREAM (zs) ) algorithm to estimate eight CLM v.4.5 ecosystem parameters using 1 year records of half-hourly net ecosystem CO 2 exchange (NEE) observations of four central European sites with different plant functional types (PFTs). The posterior CLM parameter distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 104 publications
(179 reference statements)
0
70
0
Order By: Relevance
“…Furthermore, emulators make it possible to calibrate complex models hierarchically, which would not be computationally feasible otherwise as hierarchical Bayesian modeling involves calibrating models many times at multiple spatial/temporal/experimental settings. For example, it is a known issue that sitelevel calibrations are not easily transferable to new sites or larger scales (Post et al, 2017). In that sense, Hierarchical…”
Section: Bruteforce Vs Emulatormentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, emulators make it possible to calibrate complex models hierarchically, which would not be computationally feasible otherwise as hierarchical Bayesian modeling involves calibrating models many times at multiple spatial/temporal/experimental settings. For example, it is a known issue that sitelevel calibrations are not easily transferable to new sites or larger scales (Post et al, 2017). In that sense, Hierarchical…”
Section: Bruteforce Vs Emulatormentioning
confidence: 99%
“…For example, NEE is a result of both primary production and respiration processes, and the model outputs were sensitive to parameters involved in both of these processes. If we were to assimilate only NEE, estimated parameters contributing to NEE might have compensating errors (Post et al, 2017).…”
Section: Autocorrelation Correction and Multiple Data Constraintsmentioning
confidence: 99%
“…On the other hand, if the calibration data are sensitive to the parameters, even a complex model can sometimes be well constrained by using a single type of observations. For example, Post et al (2017) estimated eight CLM parameters using 1-year records of half-hourly NEE observations at four sites, and found that for most sites the CLM parameters can be well constrained with their 95 % confidence intervals close to the maximum a posteriori estimates. For the only site where the parameter uncertainties were relatively large, they concluded that the simulated NEE was less sensitive to these parameters.…”
Section: Synthetic Study With Pseudo-datamentioning
confidence: 99%
“…Thus, the DREAM scheme is particularly applicable to complex and multimodal optimization problems. Recently, Post et al (2017) reported a successful application of DREAM in estimation of the complex Community Land Model (CLM) using 1-year records of NEE observations. They found that the posterior parameter estimates were superior to their default values in the ability to track and explain the measured NEE data.…”
Section: Introductionmentioning
confidence: 99%
“…The model used was CLM4.5 and compared with EC measurements and LAI from the RapidEye satellite. We applied successfully validated parameter estimates from Post et al (2016) for C 3 grass, evergreen coniferous forest and broadleaf deciduous forest. For C 3 crops, we estimated a new set of parameters as the estimated parameters by Post et al (2016) did not improve the model-data fit in verification experiments, using the DiffeRential Evolution Adaptive Metropolis (DREAM; Vrugt, 2015).…”
mentioning
confidence: 99%